2011
DOI: 10.1111/j.1365-2125.2010.03822.x
|View full text |Cite
|
Sign up to set email alerts
|

Case series on a diversity of illicit weight‐reducing agents: from the well known to the unexpected

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT Adulteration of over‐the‐counter proprietary medications has been reported previously. However, to date a detailed study specifically on illicit slimming products has been lacking. WHAT THIS STUDY ADDS This study showed the presence of a wide variety of illicit weight‐reducing agents in over‐the‐counter slimming products, including registered or banned drugs and pharmaceutical analogues. These products may result in significant toxicities and even mortality. AIMS To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 9 publications
1
29
0
3
Order By: Relevance
“…In the present study, 60% slimming products were found to contain with sibutramine and/or phenolphthalein although they have been banned by the Food and Drug Administration (FDA). A study conducted in Hong Kong reported that the presence of these illicit chemicals resulted in high mortality and morbidity [4]. Another study on the slimming products also showed the presence of sibutramine in high concentrations (2400 µg/g) comparable to our study where the highest concentration of sibutramine was also estimated to be 2846 µg/g.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In the present study, 60% slimming products were found to contain with sibutramine and/or phenolphthalein although they have been banned by the Food and Drug Administration (FDA). A study conducted in Hong Kong reported that the presence of these illicit chemicals resulted in high mortality and morbidity [4]. Another study on the slimming products also showed the presence of sibutramine in high concentrations (2400 µg/g) comparable to our study where the highest concentration of sibutramine was also estimated to be 2846 µg/g.…”
Section: Resultssupporting
confidence: 72%
“…These products are often advertised to contain purely natural ingredients, hence assumed to be harmless. However, many such products have been reported to contain various illicit agents, including sibutramine, diethylpropion, phenolphthalein, fenfluramine, N-nitroso-fenfluramine, phentermine phenytoin, and even animal thyroid tissue posing a health risk on prolonged usage [1][2][3][4][5][6]. One study reported that the presence sibutramine and phenolphthalein resulted in high mortality and morbidity in Hong Kong population [4].…”
Section: Abstract: Slimming Products Sibutramine Phenolphthaleinmentioning
confidence: 99%
“…2,3 However, many weight loss supplements have been found to contain a variety of banned pharmaceutical ingredients, some of which have led to life-threatening adverse reactions and deaths. [4][5][6] Since 2005, the US Food and Drug Administration (FDA), as well as European regulatory agencies, have identified over 300 such pharmaceutically adulterated weight loss supplements. 7,8 A wide variety of banned compounds have been identified including sibutramine, cetilistat, rimonabant, fenproporex, phenolphthalein, and many others.…”
mentioning
confidence: 99%
“…For the general public, a simple rule can be taught: if it sounds too good to be true, it probably is; and this is especially so for pCMs that claim to treat certain conditions in which western-drug adulteration is common, for example, weight reduction and diabetes, as previously reported by our unit, 10,11 and pain, respiratory conditions, and skin problems, as reported in the present study. It is prudent to consider brands and retailers that are trustworthy and, in case of doubt, patients should seek opinion from their primary care doctors.…”
Section: Discussionmentioning
confidence: 70%